Contrasted histories of organelle and nuclear genomes underlying physiological diversification in a grass species. Issue 1938 (11th November 2020) - Bianconi, Matheus E.; Dunning, Luke T.; Curran, Emma V.; Hidalgo, Oriane; Powell, Robyn F.; Mian, Sahr; Leitch, Ilia J.; Lundgren, Marjorie R.; Manzi, Sophie; Vorontsova, Maria S.; Besnard, Guillaume; Osborne, Colin P.; et al.
Abstract : C4 photosynthesis evolved multiple times independently in angiosperms, but most origins are relatively old so that the early events linked to photosynthetic diversification are blurred. The grass Alloteropsis semialata is an exception, as this species encompasses C4 and non-C4 populations. Using phylogenomics and population genomics, we infer the history of dispersal and secondary gene flow before, during and after photosynthetic divergence in A. semialata . We further analyse the genome composition of individuals with varied ploidy levels to establish the origins of polyploids in this species. Detailed organelle phylogenies indicate limited seed dispersal within the mountainous region of origin and the emergence of a C4 lineage after dispersal to warmer areas of lower elevation. Nuclear genome analyses highlight repeated secondary gene flow. In particular, the nuclear genome associated with the C4 phenotype was swept into a distantly related maternal lineage probably via unidirectional pollen flow. Multiple intraspecific allopolyploidy events mediated additional secondary genetic exchanges between photosynthetic types. Overall, our results show that limited dispersal and isolation allowed lineage divergence, with photosynthetic innovation happening after migration to new environments, and pollen-mediated gene flow led to the rapid spread of the derived C4 physiology away from its region of origin.